2003
DOI: 10.1034/j.1600-0668.2003.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

House dust-mite allergen and cat allergen variability within carpeted living room floors in domestic dwellings

Abstract: Exposure to allergens from house dust-mites (Der p 1) and domestic cats (Fel d 1) is associated with symptom severity in atopic subjects with asthma and rhinitis. Assessment of allergen exposure in the domestic environment is normally determined by measurement from a single floor site. We determined the variability of these allergens and protein throughout the whole living room floor area. Dust samples were collected from 1 m2 areas from 16 carpeted living room floors in Wellington, New Zealand, and analyzed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Loan et al collected dust from 16 living room floors that were divided into sections of 1 m 2 and analyzed each section for dust weight and concentrations of Der p 1 and Fel d 1. The authors found that the assumption that a sample from a central area of the living room floor was representative of the whole room was correct for Der p and Fel d 1 (Loan et al, 2003). Simpson et al however found considerably larger variability for the living room and bedroom floors for Der p 1 but this variability was less in the immediate area around soft furnishings and beds than the rest of the room (Simpson et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Loan et al collected dust from 16 living room floors that were divided into sections of 1 m 2 and analyzed each section for dust weight and concentrations of Der p 1 and Fel d 1. The authors found that the assumption that a sample from a central area of the living room floor was representative of the whole room was correct for Der p and Fel d 1 (Loan et al, 2003). Simpson et al however found considerably larger variability for the living room and bedroom floors for Der p 1 but this variability was less in the immediate area around soft furnishings and beds than the rest of the room (Simpson et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…One of the assumptions common to most epidemiological studies to date is that the concentration of allergens measured in dust samples collected by vacuuming a single 1 m 2 of settled dust reservoir such as carpet or mattress is a good marker (or ‘index’) of chronic personal exposure. However, it has been clearly demonstrated that there is a huge variation in mite allergen levels between different areas within a single room, suggesting that it is unlikely that a single sampling site is representative for the assessment of individual's exposure . For example, one study has reported a mean coefficient of variation of > 80%, with up to 192‐fold difference in allergen concentrations between dust samples collected from the different square metre areas within the same rooms .…”
Section: Index Of Allergen Exposurementioning
confidence: 99%
“…The variability in the levels measured, even within the same room (Loan, Siebers, & Fitzharris, 2003) and during different seasons (Chen, Su, & Lin, 2002), limits the usefulness of such studies in the evaluation of the true exposure risk. This approach, however, remains the most common practice in the field.…”
Section: Introductionmentioning
confidence: 95%